Biosorption of lead (II) from aqueous solutions by dried water hyacinth (Eichhornia Crassipes) - Siti Aishah, Abd Wahid (2009)
The contamination of wastewaters, river sediments and soil with toxic metals is a complex problem. The removal of these contaminations has received much attention in recent year using conventional methods such as chemical reduction, ion exchange and electrochemical treatment. The alternative methods is discovered which is biosorption, refer to the physics-chemical binding of metal ions to biosorbent. It is a relatively new process that has been proven very promising in the removal of contaminants from aqueous effluents. It has been shown to be an economically feasible alternative method for removing heavy metals (Sabriye et al., 2005). Water hyacinth approaches being a scourge in many parts of the world, choking waterways and hindering transport upon them. The usefulness of the biosorbent of water hyacinth roots in removing metal ions from solution was investigated recently and it was shown that the roots have the potential of being used as a cheap source of biosorbent for metal ions (Kaustubha et al., 2005). The purpose of this study is to investigate the ability of dried water hyacinth (Eichhornia Crassipes) as biosorbent in biosorption of Lead (II) from aqueous solution. This study is a small scale research that might be practice in wastewater plant. The effect of physic-chemical parameters like biosorbent dosage, initial concentration, pH and contact time were investigated. The analysis was done by using Atomic Absorption Spectroscopy. From the result obtained, the removal of Pb (II) ions was optimum when initial lead concentration was almost 40 mg/ L, biosorbent dosage at 0.225 g, pH 5.5 and at 8 minutes contact time. Other process conditions were optimized. These were volume of sample: 40 mL, temperature: 25○C and agitation speed: 120 rpm. In this study, it is shows that a biomaterial produced from dried water hyacinth can provide a simple, effective and yet cheaper method in removing lead from contaminated water.